Burnout Syndrome in the Performance of the Labor Activities of the Teachers of the Modality of Present Education of the Department of Human and Social Sciences of the Universidad de las Fuerzas Armadas - ESPE - Mora Ortiz, Lucy (2016)
The present study seeks to determine the presence of Burnout Syndrome and its impact on the performance of the teachers of the Department of Humanities and Social Sciences of the Universidad de las Fuerzas Armadas-ESPE. It is a descriptive, explanatory, correlational, and analytical study which allowed an overview of psychosocial risks, specifically syndrome of Burnout, as an effect of overexposure that affects teachers. The sample was formed by 40 teachers from the full-time modality. The instruments used in gathering information were: the questionnaire of Maslach Burnout Inventory for teachers adapted by Bazarra (2003) and the survey of teacher performance; procedure of data and the analysis used statistical program SPSS v.2.0 and Excel. The results determined that teachers maintain an excellent qualification in the dimensions of performance such as capacities and teaching skills and attitude of the teacher. The dimensions of Burnout Syndrome average in emotional exhaustion estimations was 15.58; depersonalization 42,93; 2.6 and personal accomplishment with 47.5% and 2.5% of teachers in low and fairly level of Burnout, that can be potential generators of the syndrome. In this case, programs and plans that minimize this psychosocial risk factor to prevent damages to health should be run in order to maintain the condition of improvement of the quality of life of the teacher.